A State of Art on Energy Efficient Multipath Routing In Wireless Sensor Networks - Swedika Sharma (International Journal of Informatics and Communication Technology (IJ-ICT), 2018)
Wireless sensor network is the combination of sensor nodes where sensor nodes are distributed all over the network. There are some challenges that come into the wireless sensor network n context to energy efficiency, network lifetime, storage and battery backup. The most important feature of a routing protocol, in order to be efficient for WSNs, is the energy consumption and the extension of the network’s lifetime. In this paper, we have analyzed various routing techniques for WSN that increases the network lifetime and energy consumption.